Manager-Employee Relationships: Guided by Kant's Categorical Imperative or by Dilbert's Business Principle - Borowski, Paul J. (Journal of business ethics, 1998)
The relationship between Employer and Employees is a central one in the world of business. While an important relationship, it is one that is often a source of tension for the workplace. Employers are seemingly in constant mistrust of workers, while workers often look upon their bosses as "less than competent". In the American world of business today, should this "adversarial" relationship continue or should the Employer–Employee Relationship be governed by different rules. Immanuel Kant's Categorical Imperative offers some insights into the way this relationship should be viewed. Also, the philosopher Alfred North Whitehead has some important points to add to the discussion of this crucial business relationship. A look at the case involving Malden Mills Textile Plant and its CEO Aaron Feuerstein will be used to launch this discussion.